Children with autistic spectrum disorder can imagine actions— what can this reveal about the Broken Mirror Hypothesis? - Galli, Jessica; Dusi, Laura; Garofalo, Gioacchino; Brizzi, Alessandra; Gritti, Michela; Polo, Federica; Fazzi, Elisa; Buccino, Giovanni (Frontiers in Neurology, 2025)
ObjectiveThis study investigated whether children with Autistic Spectrum Disorder (ASD) can imagine object directed actions similarly to their typically developed (TD) peers.Study designWe tested the ability to imagine goal directed actions in children with ASD (n = 18) and TD (n = 18) peers by means of VMIQ-2 questionnaire and a novel behavioral task, in which children were requested to imagine some daily actions, after seeing them through videoclips presented on a computer screen. Observed actions lasted 4 s and children were requested to follow the same time course during imagination. During this motor imagery (MI) task, children were interrupted at a specific timepoint (e.g., at 1.5 s) from the beginning of the task. Afterwards, they had to select one of two frames extracted from the videoclips: one showed the correct timepoint at which the imagined action was stopped, the other depicted an earlier or later timepoint. Children had to press the key associated to the correct frame to provide their responses.ResultsBoth groups performed similarly in the questionnaire and in the novel MI task, where they showed the same error rate. Errors distribution suggests that all children exploited a similar strategy to solve the task, being errors mainly distributed in judging the later frame.ConclusionThese findings support the view that children with ASD can imagine actions similarly to their TD peers. These results do not fully support the Broken Mirror Hypothesis and may encourage the use of MI as a cognitive strategy in the rehabilitation of autism.